THE POTENTIAL ROLE OF PANGLIMA LAÔT FOR SUSTAINABLE MARINE ECOTOURISM DEVELOPMENT BASED ON ISLAMIC CULTURE - Aswita, Dian; Apriana, Evi; Herlina, Herlina; Abubakar, Abubakar; Azzarkasyi, Muhammad (Islam Futura, 2023)
Ecotourism improvement has been a challenge in developing the community’s welfare. This study investigated the potential role of Panglima Laôt as traditional wisdom for the sustainable development of marine ecotourism. Its role was responsible for a sustainable environment and preservation of culture through a traditional approach. Teupin Layeu Iboih beach has potential and fantastic scenery on the coast and under seawater that attracts many tourists. These merits should provide many benefits for the residents in the tourist spot. In this sense, the contributions of the Panglima Laôt have appeared to improve the marine resources and the quality of the landscape in Teupin Layeu Iboih, Sabang city. The Panglima Laôt has formulated and promulgated strict regulations to encourage a sustainable coastal and marine environment. The local wisdom would increase the welfare of the people living in the coastal area, and the harmonization between humans and the biosphere can be achieved.